The state of occupational stress in medical workers, counteraction and overcoming it (Environment & Health, 2022)
Objective. To determine the manifestations and the level of predictors of the development of emotional burnout (PREV) among medical workers in the Vinnytsia region and develop preventive measures to prevent it.Materials and methods. The study involved 324 respondents - healthcare workers in the Vinnytsia region. Among the respondents were women – 82,4%, men – 17,6%. The average age of respondents among doctors was 44,06+12,2 years, among nurses – 37,2+11,4 years. The length of service in professional activities was: among doctors – 19,7 + 12,3 years and SMPs – 15,5 + 11,1 years. The psychodiagnostic method of emotional burnout by V.V. Boyko was used in the study and the adapted technique of N.E. Vodopianova. Statistical processing of the study results was performed in the licensed standardized package Statistica 6.1 for Windows with the calculation of the arithmetic mean value, the standard mean arithmetic error. The significance of the difference was assessed using Student's t-test (t). The work used content analysis of domestic and foreign scientific sources, biblio-semantic, analytical and statistical research methods.Research Results. The article analyzes the state of professional and emotional burnout/stress among medical workers in the healthcare sector in Ukraine and abroad. The chief causes of professional burnout/stress, their factors, and their consequences are highlighted.Conclusions. These research results indicate inappropriate working conditions and the presence of harmful professional factors leading to a high level of emotional exhaustion, depersonalization, and a reduction in professional achievements, which negatively affects the performance of their professional duties by every second health worker and requires them to be provided with outpatient treatment to prevent the transition of PREV syndromes and professional burnout into illness. The prospect of further research is to study the problem of professional burnout/stress, counteraction, and an effective system of mental health prevention both for medical personnel and the population of Ukraine.
Keywords: occupational stress; burnout predictors; healthcare professionals; prevention